Halal Sustainability: Pengolahan Limbah Industri Tahu dan Tempe Menjadi Tepung ALai (Ampas Kedelai) - Khozin Zaki; Anisa Muslimah; Rika Ayu Lestari; Didi Afrizal (Kreativasi : Journal of Community Empowerment, 2023)
Tofu and tempeh factories are among the many commodities in Indonesia. Waste from these factories in the form of soybean pulp has the potential to become one of the environmental pollution problems. Researchers try to process the waste into valuable products that the community can consume and have economic, namely flour. Soybean pulp flour has a protein content of 15.20-17.72% and a fairly high crude fiber content of 3.23-21.35%.  This research seeks to discover the problems of soybean mill waste, halal, and thayyiban product innovation. This sustainable halal product development innovation offer consists of the main product, flour, which can be a food additive product. The research uses an experimental method in the form of a pure experiment (true experiment) with a quantitative descriptive approach and literature study. Of the three treatments in the experiment, the first treatment (P1) is sun-dried soybean pulp with a smooth and soft texture, with the most optimal beige color and pleasant aroma. The advantages of this product package are the availability of cheap and readily available ingredients, a relatively simple process on a household scale, and clear halal and tayyib traceability as a solution to the SDGs points, production, and good health, responsible consumption and well-being.